Descended Social Anxiety Disorder and Craving in Women Heroin Dependence Through Exercise Alerts Plasma Oxytocin Levels - Wang, Jing Song; Liu, Jing Lin; Zhang, Jun; Tan, Jun; Huang, Ting; Lu, Chun Xia; Peng, Xi Yang; Guo, Yin; Zheng, Lan (Frontiers in Psychiatry, 2021)
Purpose: This study explored the association between peripheral blood oxytocin (OT) and social anxiety disorder (SAD) and cue-induced cravings in female heroin-addicts. The effect of exercise on alleviation of SAD and OT levels was also explored. Methods: A total of 72 females with heroin-dependence were assigned to three groups based on SAD severity. The three groups were Non-SAD control, SAD control, and SAD exercise groups. Subjects in SAD exercise group underwent aerobic exercise and resistance training for 8 weeks (60 minutes per day, 5 days per week). Enzyme-linked immunosorbent assay analysis and Liebowitz Social Anxiety Scale (LSAS) scores were used to determine plasma OT concentration and SAD, respectively. Cue-induced craving was assessed using Visual analogue scale (VAS) and Desires for Drug Questionnaire (DDQ). Mixed-effect analysis of variance and Pearson correlation analysis were used to explore the effect and correlation between different parameters. Results: OT levels in the SAD exercise group was significantly high after exercise (p<0.01). LSAS, VAS and DDQ (“Desire and Intention” and “Negative reinforcement”) scores in the SAD exercise group were significantly lower after exercise (p<0.01). Plasma OT level was negatively correlated with LSAS score (r=-0.534, p<0.001), VAS score (r=-0.609, p<0.001), “Desire and Intention” score (r=-0.555, p<0.001), “Negative reinforcement” score (r=-0.332, p<0.01) and positively correlated with the “control” score (r=0.258, p<0.05). LSAS was positively correlated with VAS score (r=0.588, p<0.001) and “Desire and Intention” score (r=0.282, p<0.05). Conclusions: The findings of the present study indicates that plasma OT is a potential peripheral biomarker for prediction of the severity of social anxiety in female heroin withdrawal patients. Aerobic exercise combined with resistance training plus incremental load for 8 weeks can increase plasma OT levels and significantly reduce severity of SAD and cue-induced cravings in female heroin-addicts.